Digital social networks as site of memory: citizen dialogues through photography on Facebook (2022)
This paper addresses the potential of social media as places for citizen dialogue around memory and cultural identity of territories and their inhabitants. From the perspective of cultural anthropology and memory studies, an exploratory research is presented based on the content analysis of two Facebook groups linked to the city of Cartagena de Indias (Colombia), accompanied by qualitative interviews with their administrators and with historians of the territory. The results explain some of the factors that contribute to the popularity of these virtual groups, based on the use of vernacular photography, and show how digital social networks have come to complement or replace functions that were once restricted to public and academic institutions, museums and archives. It is concluded that, despite their limitations, these groups, born in a specific historical and technological context, constitute important virtual places of memory. © 2022 Scientific Association Icono14. All rights reserved.